Influence of Composted Wastewater Sludge (CWS) on Lead and Copper Uptake by Radish (Raphanus sativus L.). Issue 4 (2nd October 2018) - Onchoke, Kefa Karimu; Urasa, Isai T.; Shipes, Barbara G.
Abstract: The potential risk of increased metal concentrations through the application of composted wastewater sludge (CWS) is of concern. In particular, the high affinity of composted wastewater sludge for metals such as Pb, may influence the extent of metal uptake by plants. In this study, a sequential extraction protocol was employed to determine the fractionation and bioavailability of Pb, Cu, Cr, Cd, Zn, Ni, and Fe in CWS. To evaluate the influence of CWS on metal uptake, a fast growing plant Raphanus sativus L. (cultivated radish), was grown in CWS amended with perlite at four different compositions (0, 25, 50, 75, 100% w/w) treated with Pb and Cu. Plants were harvested after 3 weeks and analyzed for Pb and Cu concentrations. The extent of metal uptake, and intercompetitions between Cu and Pb upon application, at pH 7.3 and 5.8 was also assessed. Best growth was apparent at 25% to 50% (w/w) CWS composition, while an increase in the pH lowered Pb and Cu concentrations in plant tissues. Higher metal concentrations were found in roots vis-à-vis shoot or leaves. In was found that longer incubation periods of more than 3 weeks are needed for metal salts supplied in the inorganic form to be incorporated into the CWS structure and reduce their uptake.